2015
DOI: 10.1111/jnc.13103
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the GABA transporter GAT‐1 ameliorates spinal GABAergic disinhibition and neuropathic pain induced by paclitaxel

Abstract: Paclitaxel is a chemotherapeutic agent widely used for treating carcinomas. Patients receiving paclitaxel often develop neuropathic pain and have a reduced quality of life which hinders the use of this life-saving drug. In this study, we determined the role of GABA transporters in the genesis of paclitaxel-induced neuropathic pain using behavioral tests, electrophysiology, and biochemical techniques. We found that tonic GABA receptor activities in the spinal dorsal horn were reduced in rats with neuropathic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 83 publications
(191 reference statements)
4
60
0
Order By: Relevance
“…GAT-1 is responsible for most of the GABA uptake from the synaptic cleft in the brain (Borden, 1996; Conti et al, 1998; Jensen et al, 2003). In the same year (2015) another group also reported increased expression of GAT-1 in the spinal cord of an animal model of PINP (Yadav et al, 2015). In addition, they observed that intrathecal injection of a GAT-1 inhibitor ameliorates PINP (Yadav et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…GAT-1 is responsible for most of the GABA uptake from the synaptic cleft in the brain (Borden, 1996; Conti et al, 1998; Jensen et al, 2003). In the same year (2015) another group also reported increased expression of GAT-1 in the spinal cord of an animal model of PINP (Yadav et al, 2015). In addition, they observed that intrathecal injection of a GAT-1 inhibitor ameliorates PINP (Yadav et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, astrocytes express GABAA and GABAB receptors (41). With expression of GABA transport, astrocytes involve in GABA uptake to regulate extracellular concentrations of GABA (42). In spare nerve injury model of neuropathic pain, GABA uptake increase with upregulation of the GABA transport 1 (GAT-1) in activated spinal astrocytes (42).…”
Section: Disinhibition Of Spinal Gabaergic Interneurons and Neuro-patmentioning
confidence: 99%
“…With expression of GABA transport, astrocytes involve in GABA uptake to regulate extracellular concentrations of GABA (42). In spare nerve injury model of neuropathic pain, GABA uptake increase with upregulation of the GABA transport 1 (GAT-1) in activated spinal astrocytes (42). In ischemic injury, activated astrocytes up-regulate the expression of GAD and GABA (43).…”
Section: Disinhibition Of Spinal Gabaergic Interneurons and Neuro-patmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanisms underlying the increased activity of superficial dorsal horn neurons in the paclitaxel-treated mice remain unclear. Yadav et al 20) reported that paclitaxel induces the expression of γ-aminobutyric acid (GABA) transporter-1 and increases the uptake of GABA. This results in decreases in GABA levels in the synaptic clefts of spinal dorsal horn neurons.…”
Section: )mentioning
confidence: 99%